Planning for service management within a service-oriented computing infrastructure a necessary infrastructure for mission critical deployment. - Jones, Bill
The more widely service oriented architectures become incorporated into core business applications and processes, the more critical the ability to easily configure, manage and monitor the overall infrastructure becomes.